OUT OF USE ISAFETCOMBINATIONS OF “BABURNAME” IN THE MODERN UZBEK (Scientific journal of the Fergana State University, 2023)
In this article the lexical and semantic features of Arabic and Persian isafet combinations are analyzed which were used in 'Baburnoma' and out of use today.